Quantum Entanglement and Encoding Algorithm - Bertini, Cesarino; Leporini, Roberto; Moriani, Sergio (International journal of theoretical physics, 2023)
Entanglement is a resource for quantum computation and information tasks. It has increasingly become clear that entanglement may be brought forth in combination of concepts as “(the) Animal Acts” or “Animal (eats) Food” rather than being unique to micro-physical systems like photons or electrons. We extend the approach to the combination of three concepts which determine non-classical statistical correlations. Moreover, we introduce a new vector encoding algorithm that takes entanglement into account.